DNA methylation of human choline kinase alpha gene - Siti Aisyah Faten Mohamed Sa'dom,; Nur Farah Hani Azemi,; Mohammad Shahrizal Mohammad Umar,; Yoke, Hiang Yee; Wei, Cun See Too; Ling, Ling Few (Penerbit Universiti Kebangsaan Malaysia, 2020)
Increased level of choline kinase (CK) is a common feature in cancers and inhibition of this enzyme has been applied as anticancer strategy. DNA methylation of gene promoter especially at CpG island is associated with suppression of gene expression. Despite the importance of CK especially the alpha isoform in cancer pathogenesis, epigenetic regulation of ckα expression has not been investigated. Hence, this study aimed to determine the effect of DNA methylation on ckα promoter activity and gene expression by using hypomethylating (5-aza) and methylating (budesonide) agents. The level of DNA methylation in the second CpG island of ckα promoter was determined by PCR-based method. 5-aza and budesonide increased the methylation of the selected CpG island compared to untreated control. Treatment with the drugs produced opposite effect, with 5-aza induced ckα promoter activity and gene expression while budesonide suppressed the promoter activity and mRNA level of this gene. Deletion of a region containing the second CpG island on ckα promoter resulted in significantly lower promoter activity. In conclusion, this study showed that DNA methylation could be one of the mechanisms that regulate the expression of ckα gene.